Efficient [5+1] Synthesis of 4-Quinolones by Domino Amination and Conjugate Addition Reactions of 1-(2-Fluorophenyl)prop-2-yn-1-ones with Amines - Iaroshenko, Viktor O.; Mkrtchyan, Satenik; Villinger, Alexander (Synthesis, 2013)
A catalyst-free synthetic approach is described for the synthesis of 4-quinolone derivatives through a tandem amination/conjugated Michael addition sequence of 1-(2-fluorophenyl)prop-2-yn-1-one derivatives. The [5+1]-cyclization proceeds efficiently at a high temperature under an inert atmosphere with lithium carbonate as a base, and it provides a practical route to a diverse range of 4-quinolones. The mechanism was studied in details and several of the intermediates were isolated.
Keywords: quinones; ketones; domino reactions; aminations; Michael additions; heterocycles